DISTRIBUTION OF GASTROPODA AND ITS RELATION WITH ENVIRONMENTAL CHARACTERISTICS IN COASTAL WATERS OF NUSALAUT ISLAND, CENTRAL MALUKU - Muhammad Masrur Islami (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Nusalaut Island is one of the small islands in Maluku waters that is influenced by the dynamics of Banda Sea. The aim of this study was to investigate the density and spatial distribution of gastropods and its relation with environmental characteristics using multivariate analysis i.e., Principal Component Analysis (PCA) and Correspondence Analysis (CA). This study was conducted in Nusalaut Island as a part of Marine Resources Inventory Programme in Nusalaut Island in 2009. Fieldwork was conducted in northern Nusalaut Island using systematic random sampling method. Results showed that the highest density was Nassariidae family and other low density were from the familes of Cerithiidae, Buccinidae, Terebridae, and Conidae, respectively. The environmental characteristics affected species composition and density of gastropods. Distribution of environmental characteristics and spatial distribution of gastropods at each station was influenced by a combination of several parameters. Microhabitat pattern, predatory, and human activities also affected the distribution of gastropods. Keywords: gastropoda, spatial distribution, environmental characteristics, Nusalaut Island